2013
DOI: 10.3144/expresspolymlett.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics and morphology of melt spun poly(ethylene terephthalate) nanocomposite fibers

Abstract: Abstract. Natural nanoclay closite Na + incorporated melt spun poly(ethylene terephthalate) (PET) fibers were investigated for crystallization kinetics and morphology. Nature of clay dispersion and nanocomposite morphology were assessed using wide angle X-ray diffraction (WAXD) and transmission electron microscopy (TEM). Fiber mechanical properties were measured using single fiber tensile test. Combination of scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) was used to investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…A nanoclay dispersion instead of conventional micron sized additives is currently being used to increase the opacity, modulus, tensile strength, barrier properties, flame resistance, and thermal and structural properties of many plastics. Studies have often shown enhanced properties in the final products derived by clay loading as low as 0.5 wt% compared with conventional composites with a large amount of fillers …”
Section: Introductionmentioning
confidence: 99%
“…A nanoclay dispersion instead of conventional micron sized additives is currently being used to increase the opacity, modulus, tensile strength, barrier properties, flame resistance, and thermal and structural properties of many plastics. Studies have often shown enhanced properties in the final products derived by clay loading as low as 0.5 wt% compared with conventional composites with a large amount of fillers …”
Section: Introductionmentioning
confidence: 99%
“…Samples of approximately 5 mg in weight were heated at a temperature in the 40–300 °C range in nitrogen environment at a ramp rate of 5 °C/min. The degree of crystallinity was then measured using the following equation: χ%=ΔHΔH×100 …”
Section: Methodsmentioning
confidence: 99%
“…Here χ% is the degree of crystallinity, Δ H the measured heat of fusion of the PET nonwovens, and ΔH the theoretical heat of fusion of a 100% crystalline PET sample. Note that, Δ H is measured as the area under the melting peak of the DSC curve obtained using the Universal Analysis software, and ΔH = 115 J/g for PET . It should be emphasized that the method of characterizing the degree of crystallinity by DSC should only be used in a comparative study of the same polymer samples.…”
Section: Methodsmentioning
confidence: 99%
“…The scattered phase should be used in a quantity not lower than the percolation threshold. The value of Electrical Properties of Polyesters http://dx.doi.org/10.5772/intechopen.78612 percolation threshold depends on the coefficient of the shape of conducting particles, their dimensions and arrangement in the matrix [54][55][56]. Particularly beneficial is the use of nanophase scattered in PET and PLA [57][58][59][60][61][62][63][64].…”
Section: Imparting Electro-conductive and Antistatic Properties To Pomentioning
confidence: 99%